Bioactive substances in the stratum corneum of the epidermis found as indicators of skin damage due to sun exposure. Issue 3 (25th October 2021) - Fukunaga, Atsushi; Fukushima, Satoshi; Iwata, Hiroaki; Nakahara, Makiko; Sasaki, Rikako; Baba, Naoko; Matsunaka, Hiroshi; Murakami, Yumi; Furue, Masutaka; Nishigori, Chikako
Abstract: Background/Purpose: Although an inflammatory response upon acute injury caused by ultraviolet radiation (UV) can be observed immediately, the influence of long‐term, repetitive low‐dose UV exposure on the skin cannot be precisely perceived, making early detection of chronic damage difficult. This study investigated bioactive substances in the stratum corneum as a potential early and sensitive indicator of the influence of sun exposure on the skin using receiver operating characteristic (ROC) analysis. Methods: Receiver operating characteristic analysis was performed to assess the responsiveness of cytokines [interleukin (IL)‐1α, IL‐1 receptor antagonist (IL‐1ra), IL‐10, tumor necrosis factor (TNF)‐α], BCL2‐associated protein X (Bax), Toll‐like receptor (TLR)3, and TLR4 in the stratum corneum of healthy people exposed (dorsum of the hand) and unexposed (inner arm) to UV. Sunscreen was applied to patients with photodermatosis for 4 weeks to evaluate changes in IL‐1ra/IL‐1α, TNF‐α, Bax, and TLR3 levels after sunscreen application, as these molecules exhibited high responsiveness to sun exposure according to ROC analysis. In addition, IL‐1ra, IL‐1α, and IL‐10 levels were quantified by enzyme‐linked immunosorbent assay, and TNF‐α, Bax, TLR3, and TLR4 levels were semi‐quantitatively assessed by immunocytochemistry. Results: Receiver operating characteristic analysis identified IL‐1ra/IL‐1α, TNF‐α, Bax, and TLR3 in the stratum corneum as highly responsive to sun exposure. Moreover, in participants, including patients with photodermatosis, IL‐1ra/IL‐1α, TNF‐α, and Bax levels decreased significantly after sunscreen application. Conclusion: The results revealed that IL‐1ra/IL‐1α, TNF‐α, and Bax in the stratum corneum represent sensitive indicators of the influence of sun exposure on the skin.